The influence of servant leadership through job engagement and organizational citizenship behavior as intervening variables on employee performance (a study on pt. Ahs kota serang) - Sucipto, Ade Hary; Sanusi, Fauji; Imron, Ali (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the influence of Servant Leadership on Employee Performance, with Job Engagement and Organizational Citizenship Behavior (OCB) as the mediating variables in PT. AHS, Serang City. This study examined fluctuations in employee performance influenced by leadership style, work engagement, and organizational civic behavior with 124 respondents. The method used is quantitative with data analysis using SmartPLS 4. Based on the results of hypothesis testing, Servant Leadership has a positive and significant influence on Employee Performance, Job Engagement, and OCB. In addition, Job Engagement and OCB have been proven to mediate the influence of Servant Leadership on Employee Performance. The results of the bootstrapping test showed that the statistical T-value for the direct relationship of Servant Leadership to Employee Performance was 0.023 (smaller than the T of table 1.960) and the P-value was 0.981 (greater than 0.05), indicating no significant effect. The test also shows that both Job Engagement and OCB have an important role as mediators that strengthen the relationship between Servant Leadership and Employee Performance